The Development of Problems for ‘Asesmen Kompetensi Minimum’ Type Based on Ethnomathematics about Farmer Activities in Aceh Besar Regency - Anggun Salsabila; Rahmah Johar; Yuhasriati Yuhasriati; Safrida Yanti; Suryawati Suryawati (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
Minimum Competency Assessment or Asesmen Kompetensi Minimum (AKM)  is used as a national assessment by involving several contexts; one of them is social culture. However, social cultural-based AKM problems, including ethnomathematics, are still limited. Therefore, efforts that can be carried out is designing ethnomathematics-based AKM problems related to farmers’ activities. This study aimed to obtain problems for ethnomathematics-based AKM problems about farmer activities in Montasik, Aceh Besar Regency, Indonesia. This research is a developmental research that was carried out through several stages, namely the preliminary, self-evaluation, prototyping, and the field test stages. In this case, the research subjects involved were 33 students of grade 8 at a junior high school in Montasik. The data analysis technique used was the Aiken's V formula and the product moment correlation. The results obtained 10 problems for ethnomathematics-based AKM about farmer activities in Montasik that achieved valid criteria and potential effects. The problems can be further used by mathematics teachers to improve the students’ numeration.Asesmen Kompetensi Minimum (AKM) digunakan sebagai asesmen nasional yang melibatkan beberapa konteks, salah satunya sosial budaya. Namun soal AKM berbasis sosial budaya termasuk etnomatematika masih terbatas. Oleh karena itu, upaya yang dapat dilakukan yaitu merancang soal tipe AKM berbasis etnomatematika terkait aktivitas petani. Tujuan penelitian ini yaitu untuk memperoleh soal tipe AKM untuk kelas 8 berbasis etnomatematika terkait kegiatan petani di Kecamatan Montasik, Kabupaten Aceh Besar, Indonesia. Penelitian ini merupakan penelitian pengembangan dengan tahapan yaitu preliminary, self evaluation, prototyping, dan field test. Subjek penelitian ini yakni 33 siswa kelas 8 dari salah satu SMP di Montasik. Teknik analisis data menggunakan formula Aiken’s V dan uji korelasi product moment. Hasil penelitian berupa soal tipe AKM berbasis etnomatematika pada kegiatan petani di Montasik sebanyak 10 soal yang valid dan memiliki efek potensial. Soal tersebut dapat digunakan oleh guru matematika untuk meningkatkan numerasi siswa.